Sociocultural and ecological factors influencing management of edible and non-edible plants: the case of Ixcatlán, Mexico - Selene Rangel-Landa; Alejandro Casas; Eduardo García-Frapolli; Rafael Lira (BMC, 2017)
Abstract Background Identifying factors influencing plant management allows understanding how processes of domestication operate. Uncertain availability of resources is a main motivation for managing edible plants, but little is known about management motives of non-edible resources like medicinal and ceremonial plants. We hypothesized that uncertain availability of resources would be a general factor motivating their management, but other motives could operate simultaneously. Uncertainty and risk might be less important motives in medicinal than in edible plants, while for ceremonial plants, symbolic and spiritual values would be more relevant. Methods We inventoried edible, medicinal, and ceremonial plants in Ixcatlán, Oaxaca, Mexico, and conducted in-depth studies with 20 native and naturalized species per use type; we documented their cultural importance and abundance by interviewing 25 households and sampling vegetation in 33 sites. Consumption amounts and preferences were studied through surveys and free listings with 38 interviewees. Management intensity and risk indexes were calculated through PCA and their relation analyzed through regression analyses. Canonical methods allowed identifying the main sociocultural and ecological factors influencing management of plants per use type. Results Nearly 64, 63, and 55% of all ceremonial, edible, and medicinal wild plants recorded, respectively, are managed in order to maintain or increase their availability, embellishing environments, and because of ethical reasons and curiosity. Management intensity was higher in edible plants under human selection and associated with risk. Management of ceremonial and medicinal plants was not associated with indexes of risk or uncertainty in their availability. Other sociocultural and ecological factors influence management intensity, the most important being reciprocal relations and abundance perception. Conclusions Plant management through practices and collectively regulated strategies is strongly related to control of risk and uncertainty in edible plants, compared with medicinal and ceremonial plants, in which reciprocal interchanges, curiosity, and spiritual values are more important factors. Understanding how needs, worries, social relations, and ethical values influence management decisions is important to understand processes of constructing management strategies and how domestication could be started in the past and are operated at the present.